The Readiness of Natural Science Secondary School Teachers in Distance Learning during the Covid-19 Pandemic - Nur Efendi; Septi Budi Sartika; Noly Shofiyah (Scientiae Educatia: Jurnal Pendidikan Sains, 2020)
The purpose of the research is to describe the readiness of secondary school teachers in East Java in distance learning during the covid-19 pandemic and the teachers' efforts in East Java in learning during the covid-19 pandemic. The research method was survey research with a sample of 70 secondary schools of natural science teachers in East Java. The data was collected by distributing questionnaires with a Likert scale. The collected data was then analyzed using descriptive statistics with Aydin & Tasci model. The results showed that secondary school science teachers in East Java were ready for distance learning, with a score of 3.45 and performing distance learning using the Google Classroom app with a percentage of 71.8% during the covid-19 pandemic. To face distance learning obstacles, the teachers can create modules for all topics of natural science at secondary school. The created module can be uploaded on an e-learning platform or WhatsApp Group. Besides, to minimize internet network use and the lack of communication tools, offline learning can be conducted, especially for natural science learning through a practicum. Furthermore, these results can be used as the basis for developing teacher resources through the enrichment of teaching models and strategies that can be applied under any circumstances in the event of a pandemic.